The last colour to fade - Visagie, Morne (Michaelis School of Fine Art, 2020)
Drawing on personal recollections and collective history, The Last Colour to Fade offers a meditation on the sea as both a physical and psychological landscape. Memories of my childhood spent on Robben Island are interwoven with historical facts, with narratives borrowed from literature and film, and images from art and life. Shifting between first person and third, between my own reflections and those of others, I have found in the lives and works of Adriaan Van Zyl, Derek Jarman, Jean Genet, Virginia Woolf and others a shared affinity for water. The sea – changeable, inconstant – reveals itself to be evocative of not only promise and peril, but of sensuality, desire and eroticism. It offers as imperfect parallel the image of the swimming pool and its attendant changing room, evoking a history of the queer body in art and writing. The twelve discrete artworks collected under the title The Last Colour to Fade, are abstracted interpretations of these themes, where colour and materiality are primary. The works share a persistent seriality, with the recurring image of a pool, the motif of tiles, and repetition of form. Most tends towards fragility, towards a suggested impermanence, made from tissue paper, porcelain, or stained tarlatan cloth. The accompanying text is one of fragments and vignettes, which suggest rather than state my thematic concerns, pairing my own voice with those of others in quoted passages and poems. Both my exhibition and writing gesture to the liminal space between what is said and what is left unspoken.